2008
DOI: 10.1080/15567030701773806
|View full text |Cite
|
Sign up to set email alerts
|

Waterflood Profiles and Oil Recovery with Vertical and Horizontal Wells

Abstract: Experimental and numerical study is conducted to investigate the performance of a horizontal well during waterflooding of a sandstone outcrop. Three different well configurations, viz., vertical injection-vertical production (VI-VP), vertical injection-top horizontal production (VI-HPT), and vertical injection-bottom horizontal production (VI-HPB) are considered. The commercial simulator, ECLIPSE, is used for the numerical study, and history matching technique has been used to obtain the relative permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…It can be observed that the first two water flooding runs ended with recovery around 60% and 75% for Run #1 and Run #2, respectively. The obtained numbers were similar to the published data for unconsolidated sand packs with similar properties. It was observed that after 2 PV of injection of water, the ultimate recovery increased by only 6% and 8% for Run #1 and Run #2, respectively. The data suggest that the pore volumes used in the experiments and the corresponding increase in the recovery are similar to the field applications .…”
Section: Experimental Validation Of the Core Flooding Systemsupporting
confidence: 88%
See 2 more Smart Citations
“…It can be observed that the first two water flooding runs ended with recovery around 60% and 75% for Run #1 and Run #2, respectively. The obtained numbers were similar to the published data for unconsolidated sand packs with similar properties. It was observed that after 2 PV of injection of water, the ultimate recovery increased by only 6% and 8% for Run #1 and Run #2, respectively. The data suggest that the pore volumes used in the experiments and the corresponding increase in the recovery are similar to the field applications .…”
Section: Experimental Validation Of the Core Flooding Systemsupporting
confidence: 88%
“…The core holder, shown here, is designed to perform one-dimensional core flooding experiments. However, any other two-dimensional or three-dimensional , core holders, as and when available, can be plugged into the system through appropriate connections to 3.175 mm (1/8 in) stainless steel tube. The dimensions of the core holder used here as an example are length = 284 mm (11.18 in) and diameter = 38.1 mm (1.5 in).…”
Section: New Core Flooding Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This will allow researchers to perform laboratory core ooding experiments, which are commonly conducted by petroleum reservoir engineers for studies related to the crude oil and gas recovery. [25][26][27][28][29] In such cases, the reservoir is mimicked by packing sand particles [27][28][29] or by using an actual core sample from the reservoir. 25,26,30 Such a technique provides an effective means to understand and quantify the oil/gas recovery process due to a ooding uid.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] In such cases, the reservoir is mimicked by packing sand particles [27][28][29] or by using an actual core sample from the reservoir. 25,26,30 Such a technique provides an effective means to understand and quantify the oil/gas recovery process due to a ooding uid.…”
Section: Introductionmentioning
confidence: 99%